Effects of financial inadequacies on the quality of secondary education: Hurungwe, Zimbabwe - Farisai Mugabe Dzoserai; Nelia Eta Marima; Nothando Msipah (Goodwood Publishing, 2025)
Purpose: The study aims to identify the effects of inadequate funding on the quality of secondary education in Hurungwe District, Zimbabwe. Research methodology: The study had a mixed approach to collecting data. A triangulation of methods was adopted to collect by using both primary and secondary methods. A pragmatist view of the study was taken. Results: Low secondary education budget allocation, inconsistent and delayed government levy payments, declining donor funding, an unfavorable economic climate where parents cannot afford levies resulting in high school dropout rates, inadequate teaching and learning resources, low pass rates, and low affiliation payments are the main causes of underfunding. Limitations: lack of a proper data recording and management system at the district offices to provide actual statistics of revenue and expenditure for schools. Contribution: Influencing policy on secondary school funding in Zimbabwe so that schools can be informed on how to come up with sustainable funding ways in order to improve the quality of education.